GPS-based Vertical Control, Unaided by a Shore Station - Byrne, John Shannon; Smith, Gail; Simmons, Walter; Mehaffey, Bill (The International Hydrographic Review, 2009)
The United States Naval Oceanographic Office (NAVOCEANO) conducts worldwide hydrographic surveys in accordance with the International Hydrographic Organization (IHO) S-44 hydrographic survey standards. The current approach to meeting IHO standards requires the use of shore-based assets to establish and maintain vertical control via in-situ water level measurements. NAVOCEANO is upgrading its shipboard mission systems to support use of the vertical component of Global Positioning System (GPS) measurements for vertical control of hydrographic survey data. The technique of utilizing the GPS measured height for vertical control is referred to as Ellipsoidal Referenced Survey (ERS). The ERS approach simplifies hydrographic survey operations by reducing the need for shore-based infrastructure for water level measurements and by allowing for the production of data products in a tactical time frame. ERS offers the potential for a more seamless vertical datum from deep water through shallow water and up onto shore. However, this approach to vertical control presents new challenges in the need to define the separation between the ellipsoid and the required vertical datum. Precise point positioning (PPP) techniques make use of GPS satellite clock corrections and satellite orbit corrections which are freely available via the Internet. PPP processing is a post-time activity, lagging data acquisition by the 18 hours to 24 hours needed to gain access to the correction values. Positioning accuracies of better than 20 cm horizontal (95% confidence) and better than 30 cm vertical (95% confidence) have been demonstrated with PPP techniques using commercial off-the-shelf (COTS) software packages. An integrated survey system configured with current state-of-the-art equipment for the sonar, motion sensor, and profiling sensor can meet IHO order 1 survey requirements using a PPP-based GPS track-line when the separation uncertainty is suitably controlled.